Strategic Approaches to Managing Education Funding for Equitable Access and Quality - Nur Hania; Mohammad Habib Imroni; Nur Anim Jauhariyah (ICO EDUSHA, 2024)
This study aims to describe and analyze strategic approaches in managing educational financing to achieve equitable access and quality education in Madrasah Tsanawiyah Wanamukti. The main focus of this research includes four key aspects: (a) transparency in financial management, (b) accountability in the use of educational funds, (c) effectiveness of fund allocation for educational programs, and (d) efficiency in the use of educational financing resources. This research employs a qualitative approach with interview, observation, and documentation methods for data collection. Data validity was tested through source triangulation involving relevant stakeholders in educational policy and financial management. The results show that educational financing management is carried out by prioritizing the principles of transparency, accountability, effectiveness, and efficiency. The success of improving access and education quality is highly influenced by the proper allocation of budgets, sound planning, and good coordination between the government, private sector, and society. The principle of transparency is realized through the openness of financial information and the involvement of various parties in decision-making processes. Furthermore, accountability and effectiveness are achieved through structured budget reporting and continuous monitoring of fund usage. Efficiency is attained through the use of technology in budget management and innovation in learning methods. Overall, strategic educational financing management has proven to be effective in creating equitable and high-quality for all students at Madrasah Tsanawiyah Wanamukti. Keywords: Education Financing, Education Quality, and Educational Equity.